Approach to amiodarone induced thyroid storm: A case report - Taylor Freeman; Jillian Pattison; Salvatore Savona; Ralph Augostini; Kyle Vankoevering (Journal of Clinical and Translational Endocrinology Case Reports, 2023)
Thyroid storm is a thyroid emergency with increased risk for mortality due to elevated levels of circulating thyroid hormone. While it can be caused by a variety of etiologies, thyroid storm secondary to amiodarone can be particularly challenging to manage. This paper describes a case of a 65-year-old man who presented from outside hospital with persistent ventricular tachycardia and multiple implantable defibrillator firings from thyroid storm following amiodarone infusion. Despite conventional first-line pharmacotherapy, he developed cardiogenic shock and multi-organ failure requiring therapeutic plasma exchange. Due to continued deterioration, he underwent emergent total thyroidectomy. Following surgery, the patient experienced clinical stabilization and has now made a complete recovery. In this paper, we highlight the complexities in the management of amiodarone induced thyrotoxicosis and offer a treatment algorithm and indications for early, definitive management with thyroidectomy.